Saliva acid phosphatases and amylase in Senoi and Aboriginal Malays and superoxide dismutase in various racial groups of Peninsular Malaysia. - Tan, Soon Guan; Teng, Yao Sheng (Springer-Verlag, 1978)
Senoi and Aboriginal Malays of Peninsular Malaysia, surveyed for saliva acid phosphatases, amylase and superoxide dismutase, were polymorphic for Sap-A and Sap-B. Senoi were also polymorphic for SOD B. Malays, Chinese and Indians from Malaysia were phenotyped for SOD A and SOD B, using saliva. Though no SOD A variant was detected in any of the three racial groups, Malays and Indians showed rare variants for SOD B.